การบริหารจัดการของสมองขั้นสูง : แนวคิดและแนวทางประยุกต์เพื่อพัฒนาการเรียนรู้ของผู้เรียน - จันทร์ขจร, เกดิษฐ์ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2019)
บทคัดย่อ การบริหารจัดการของสมองขั้นสูงเปรียบเสมือนศูนย์กลางของการควบคุมทักษะที่สำคัญที่เกี่ยวข้องกับมิติทางปัญญา และมิติทางพฤติกรรม ที่ประกอบด้วยทักษะที่สำคัญ 11 ทักษะ ส่งผลต่อพัฒนาการของเด็กในด้านการเรียน ทักษะการดำรงชีวิต คุณธรรมจริยธรรม การกำกับตนเองเพื่อให้บรรลุถึงเป้าหมาย การจัดการเรียนการสอนในศตวรรษที่ 21 มีจุดมุ่งหมายให้เด็กเกิดความสัมพันธ์ที่เชื่อมโยง ผสมผสานองค์ความรู้ซึ่งเป็นความคิดรวบยอดในศาสตร์ต่าง ๆ เข้าด้วยกัน โดยผ่านกระบวนการจัดการเรียนรู้ที่เน้นนักเรียนเป็นศูนย์กลาง เปิดโอกาสให้เด็กคิด และเรียนรู้อย่างสร้างสรรค์ การฝึกทักษะการทำงานร่วมกันเพื่อให้เด็กเกิดประสบการณ์ในการทำงานกับบุคคลที่มีความแตกต่างกับตนเองในด้านความคิด วัฒนธรรม และค่านิยม รวมถึงการผสมผสานการเรียนรู้ทักษะทางสังคมเพื่อสร้างให้เด็กเป็นพลเมืองที่มีความรับผิดชอบ (responsible citizen) แต่ก็ยังพบว่ามีเด็กอีกจำนวนไม่น้อยที่ไม่สามารถบรรลุตามจุดมุ่งหมายที่ตั้งไว้ การจัดการเรียนการสอนที่สอดแทรกการพัฒนาการบริหารจัดการของสมองขั้นสูงจึงถูกพัฒนาขึ้นโดยให้ความสำคัญกับการพัฒนาทักษะต่าง ๆ ที่มีความจำเป็นต่อการพัฒนาด้านสติปัญญา และพฤติกรรมของผู้เรียน เพื่อลดปัญหากลุ่มเด็กที่มีปัญหาด้านผลสัมฤทธิ์ทางการเรียน ด้านพฤติกรรมไม่พึงประสงค์ในชั้นเรียน และช่วยพัฒนากลุ่มเด็กที่ไม่มีปัญหาให้มีศักยภาพสูงขึ้นโดยผ่านกระบวนการการจัดการเรียนการสอนที่ครูปฏิบัติเป็นประจำทุกวัน บทความนี้นำเสนอการพัฒนาทักษะที่สำคัญของการบริหารจัดการของสมองขั้นสูงโดยนำเสนอหลักการ วิธีการคัดกรอง วิธีการจัดการเรียนการสอนเพื่อพัฒนาทักษะที่สำคัญของการบริหารจัดการของสมองขั้นสูง รวมถึงแก้ไขความบกพร่องในแต่ละทักษะ ซึ่งเป็นแนวทางที่ครูสามารถปฏิบัติได้จริงในชั้นเรียน คำสำคัญ: การประยุกต์ EF สู่ห้องเรียน การพัฒนาผู้เรียนด้วย EF ABSTRACT Executive function (EF) is an umbrella term for control some significant skills, involves cognitive and behavior dimension. Actually, children development are influenced by 11 executive function skills in terms of learning, life skills, moral and self-regulation. Nowadays, teaching and learning processes are focused on enhance an integration of the all subject concepts into prior knowledge by assimilation. The education has been an important changed in 21st century. The role of teachers must be considered, they need to concern three things in order to design the instruction in our schools and classrooms. Firstly, student-centered instruction takes to ensure that every student achieve their full potential in the section of thinking and creative learning skills. Secondly, teaching collaboration skills, students must learn how to work with other people, these strategies can reach their organization success. Then, learning social skills, teachers help students taking part in the school community for preparation students to become responsibility citizen. Although teachers perform these instructions, some students can’t achieve the objective. To design the initiative of teaching and learning processes with EF are developed to emphasis the proficiency in other skills that show significant improvement to students’ cognitive and behavior domains. This method can solve achievement and behavior problem in class. It usually brings out the best in usual students. This article aims to present the method of executive function skills development including the concept of executive function, executive dysfunction assessment, teaching and learning activities for improvement on executive function. These processes can be a guideline for teacher to develop strategies in classroom. Keywords: Integrated EF into classroom, Teaching and Learning